Patterns of Fluctuation of Employment in the European Union: National Cycles and Effects of Tertiarization - Juan R. Cuadrado-Roura; Carlos Iglesias; Raquel Llorente; Estela Barriopedro (European Regional Science Association (ERSA), 2003)
The paper has two aims. First, to study the possible relationships existing between cyclical fluctuations of employment by countries in the EU and the EU as a whole. And, second, to analyse the effects produced by the intense and increasing growth of employment in service industries in such fluctuations. In short, a first aim is to analyse the fact that cyclical movements of employment by countries (EU context)show some diffenreces and, on the second objective is to explore if the increasing presence of services in the employment structure has or not important consequences on employment fluctuations at national level. The first part of the paper analyses the cyclical fluctuations of employment in each of the EU countries, as a basis to set up the differences btw. countries and to establish the European cycle of employment. The second part is focused on the study of the apparent relationship existing between national fluctuations of employment and the structural changes as an explaining factor. Finally, the paper also analyses if there is or not a process of convergence (progressive adjustment) between the European countries and if they tend to adjust themselves to the more general trends observed. The lack of a European data-base on employment fluctuations at regional level (quarterly) impedes actually to extend the analysis to this level. Nevertheless, a case-study on a country and its regions will be included to test the differences/coincidences compared to the paper's general conclusions.
Keywords: 330